2004
DOI: 10.1177/1054773803259655
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Psychological Correlates of Sleep in HIV Infection

Abstract: Insomnia, a common problem associated with HIV disease, is most likely caused by a multitude of factors. This study investigated the correlations between a selected group of physiological and psychological factors and sleep quality in an HIV-infected population. A convenience sample of 79 ethnically diverse HIV-positive adults, ages 24 to 63, completed a number of questionnaires and released their laboratory records for CD4+ cell count and viral load information. Variables significantly related to sleep qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 38 publications
1
64
3
3
Order By: Relevance
“…Using the PSQI self-report measure, other researchers also report a range of 2 to 12 hours, with a mean of 5 to 6 hours sleep and sleep efficiency better than 85% in their samples of HIVinfected adults. 9,32 to complain about their sleep, and since their sleep efficiency was similar to the group of good sleepers, interventions may be better focused on strategies to relieve anxiety and restrict time spent in bed in order to shorten sleep onset latency. 35,36 Rather than relying solely on medication to improve sleep, cognitive behavioral therapy should also be considered, particularly in populations already burdened with medications used to manage their chronic illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the PSQI self-report measure, other researchers also report a range of 2 to 12 hours, with a mean of 5 to 6 hours sleep and sleep efficiency better than 85% in their samples of HIVinfected adults. 9,32 to complain about their sleep, and since their sleep efficiency was similar to the group of good sleepers, interventions may be better focused on strategies to relieve anxiety and restrict time spent in bed in order to shorten sleep onset latency. 35,36 Rather than relying solely on medication to improve sleep, cognitive behavioral therapy should also be considered, particularly in populations already burdened with medications used to manage their chronic illness.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disturbance is not only prevalent, but also one of the more intense and distressful symptoms experienced in this population. [8][9][10] In HIV infection, poor sleep has been associated with disease progression, medication therapy, employment status, and lack of knowledge about behaviors that promote good sleep. [11][12][13][14] The specifi c type of sleep disturbance experienced by this population needs to be better understood in order to provide the most effective intervention to improve symptoms, daytime functioning, and quality of life.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13][14][15] For example, Gay and colleagues 13 found that among a sample of 350 participants with HIV, trouble sleeping was the symptom most strongly associated with non-adherence to ART. In addition, previous research has demonstrated that poor sleep quality is associated with self-reported HIV symptom severity among adults with HIV, 17 and lower numbers of CD3 + /CD4 + cells. 18 As such, sleep disturbance may be associated with both HIV medication adherence and self-reported HIV symptom severity.…”
Section: Introductionmentioning
confidence: 99%
“…9 In fact, up to 73% of HIV-positive individuals report significant sleep disturbance, 10 thus rendering poor sleep as one of the most prevalent and debilitating HIV symptoms in both intensity and severity. 11,12 In addition to daytime fatigue, a breadth of research has demonstrated that disturbed sleep, among individuals with HIV, is associated with non-adherence to ART, [13][14][15] increased disease progression, 16,17 and decreased immune functioning, 18 both pre-and post-modern ART era. [10][11][12][13][14][15] For example, Gay and colleagues 13 found that among a sample of 350 participants with HIV, trouble sleeping was the symptom most strongly associated with non-adherence to ART.…”
Section: Introductionmentioning
confidence: 99%